Metaverse in the Play: A Platform for Entrepreneurship and Innovation - Lawal, Saheed Oluwaseun; Abdulkareem, Habibat Bolanle (Jurnal Pendidikan Manajemen Perkantoran, 2024)
The Metaverse, a virtual environment that combines augmented reality (AR), virtual reality (VR), and other immersive technologies, has emerged as a promising platform for entrepreneurship and innovation. This paper explores the role of the Metaverse as a playground for entrepreneurial activities, fostering creativity, collaboration, and the development of innovative ventures. The Metaverse offers entrepreneurs a unique opportunity to break free from traditional physical limitations and explore new frontiers of business creation. Through virtual interaction and engagement, entrepreneurs can transcend geographical boundaries, connecting with a global audience and accessing a diverse pool of resources, expertise, and markets. Furthermore, the immersive nature of the Metaverse provides entrepreneurs with novel ways to showcase and distribute their products and services. By leveraging AR and VR technologies, entrepreneurs can create engaging and interactive experiences that captivate customers and differentiate their offerings in the digital realm. Collaboration is another key aspect of the Metaverse as a platform for entrepreneurship. Entrepreneurs can form virtual teams, collaborate with experts from various fields, and engage in co-creation, leveraging the collective intelligence and talents available within the Metaverse community. This collaborative environment fuels innovation and enables the rapid prototyping and iterative development of novel ideas and solutions. However, while the Metaverse presents exciting opportunities, it also raises important considerations. Ethical and privacy concerns, ensuring inclusivity, and addressing potential inequalities are crucial aspects that need to be carefully navigated. In conclusion, the Metaverse is a playground for entrepreneurship and innovation, offering a fertile ground for entrepreneurial activities. By leveraging its immersive technologies, global connectivity, collaborative potential, and innovative capabilities, entrepreneurs can harness the power of the Metaverse to create transformative ventures that shape the future of business and society